Решите уравнение (3х-1)(2х+3)=3(2х-1)

0 голосов
32 просмотров

Решите уравнение (3х-1)(2х+3)=3(2х-1)


Алгебра (29 баллов) | 32 просмотров
Дано ответов: 2
0 голосов
  1. 6x^{2} +9x-2x-3=6x-3 6x^{2} +9x-2=6x 6x^{2}+7=6x
[tex]6x^{2}+7=6x6x^{2} +7x-6x=06x^{2} +x=0
[tex]x=06x+1=0x=0x=-\frac{1}{6}image
  2. x_{2} =0" alt="x_{1} =-\frac{1}{6} \\
  3. x_{2} =0" align="absmiddle" class="latex-formula">
(14 баллов)
0 голосов

6х^2+9х-2х-3=6х-3

6х^2+7х-3-6х+3=0

6х^2+х=0

Х*(6х+1)=0

Х=0

6х+1=0

6х=-1

Х=-1/6

(2.4k баллов)